Preparation method and application of carbon nano tube coated iron-nickel alloy material growing on foamed nickel in situ
By growing carbon nanotube coated iron-nickel alloy materials in situ on nickel foam, the problems of complex preparation process, serious pollution, high energy consumption and difficult recycling of existing bimetallic materials are solved, and the high activity and wide application prospects of the materials are achieved, which are suitable for large-scale production.
Patent Information
- Application Number
- CN202411615564.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-25
AI Technical Summary
The preparation process of existing bimetallic materials is complex, has severe pollution, high energy consumption, difficult recycling and difficult to achieve large-scale production.
By growing carbon nanotube-coated iron-nickel alloy material on nickel foam in situ, hydrothermal reaction and calcined gas diffusion method are used to simplify the preparation process, reduce environmental pollution, and improve material performance.
It realizes the high activity and wide application prospects of materials, simplifies the preparation process, reduces energy consumption and pollution, and is suitable for large-scale production.
Smart Images

Figure CN119506875A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of an iron-nickel alloy material coated with carbon nanotubes grown in situ on nickel foam, belonging to the technical field of new nano materials. Background Art
[0002] In the face of increasingly severe energy and environmental problems, the development of clean and sustainable monolithic materials is particularly important. Active components and material carriers are key considerations in the design of monolithic materials. Transition metal-anchored nitrogen-doped carbon has rich carbon content and uniformly distributed MN x Active sites have attracted extensive attention. This material has improved conductivity and durability. However, single-atom materials may face limitations in practical applications, such as adsorption catalysis. The coordination of multiple metals can produce a wider range of active sites, enhance electronic conductivity, and facilitate catalytic applications. In bimetallic composites, iron-nickel alloys show good catalytic activity and stability due to their low price and synergistic effect, while reducing the dissolution of metal ions. However, its low conductivity, limited specific surface area, and poor stability in alkaline solutions restrict its practical application. To solve these problems, the development of carbon-coated iron-nickel alloy nanostructures is an effective solution because carbon can enhance the conductivity of the material while protecting the metal core from peeling and corrosion. However, many bimetallic carbon materials exist in the form of granular powders, which leads to the aggregation of active sites and reduces their exposure. Patent CN118059869A discloses a catalyst and a preparation method of a carbon nanotube encapsulated alloy material. The material is in powder form, which may lead to the aggregation of active sites and is not easy to recover in practical applications, causing environmental pollution. Therefore, it is crucial to find a suitable carrier to achieve effective dispersion of active ingredients and recovery of materials.
[0003] Foam metals, especially nickel foam materials, are widely used in the fields of nanostructure penetration, heat exchange and catalysis due to their three-dimensional channels, excellent thermal conductivity, low density, high porosity and strong mechanical strength. However, the use of nickel foam as a carrier for material preparation still faces challenges, such as incomplete contact between the substrate and the active component, as well as the complexity of the manufacturing process. The use of binders limits the performance, especially long-term durability. Patent CN116005191A proposes a method for preparing an iron-based @ carbon / nickel foam composite catalyst based on waste lithium iron phosphate electrode materials. In this process, an organic binder is dissolved in a solvent, and then waste positive electrode powder is added. The slurry is made by ultrasonic dispersion or stirring, and then the slurry is evenly coated on the nickel foam. The use of binders may lead to problems such as insufficient bonding strength, limited high and low temperature resistance, easy aging and environmental pollution. Patent CN111498952A discloses a porous carbon-iron-nickel alloy foam nickel electrode and its preparation method. The triblock copolymer F127 is used as a template, which may leave residues and have an adverse effect on the experiment. In addition, the cost is high and the synthesis time is long, which is not conducive to large-scale production. The preparation method of the NiPd nano alloy catalyst introduced in patent CN114950476A requires chemical vapor deposition and electrical exchange to react with Pd hydrochloric acid solution. This method has high energy consumption and high production cost, which limits its large-scale application. Growing active species directly on the substrate can effectively solve these problems, but related research is still relatively scarce.
[0004] In recent years, monolithic materials have shown good application prospects as emerging catalysts in various advanced oxidation technologies of periodate. Advanced oxidation technologies based on periodate can produce highly active species and effectively remove organic pollutants in the environment. Traditional periodate activation methods, such as ultraviolet irradiation, freezing and alkaline methods, although effective, are difficult to apply on a large scale due to limitations such as high cost, many by-products and low reaction rate. In order to solve these problems, the use of catalysts to activate periodate to produce active substances to degrade organic pollutants has gradually attracted attention due to its advantages such as easy control and high catalytic efficiency. Therefore, it is crucial to invent a carbon-coated metal alloy monolithic material that is cheap, easy to control, easy to prepare and does not require the introduction of binders and templates to promote the application of periodate activation technology. By optimizing the structure and composition of the material, the activity and stability of the catalyst can be significantly improved, thereby achieving efficient degradation of organic pollutants. Summary of the invention
[0005] In view of the shortcomings of the existing bimetallic materials, such as complex preparation process, serious pollution, high energy consumption, difficult recycling and difficulty in large-scale production, the present invention proposes a preparation method and application of an iron-nickel alloy material coated with carbon nanotubes grown in situ on nickel foam, aiming to make the prepared material have high activity and show broad prospects in various applications. Specifically, the present invention optimizes the reaction conditions and material composition, simplifies the preparation process, reduces environmental pollution, and improves material performance to achieve economically feasible large-scale production.
[0006] To solve the above problems, the present invention adopts the following technical solutions:
[0007] The method for preparing the carbon nanotube-coated iron-nickel alloy material grown in situ on nickel foam of the present invention comprises the following steps:
[0008] Step 1: The nickel foam material is ultrasonically cleaned in hydrochloric acid aqueous solution, acetone, deionized water and anhydrous ethanol in sequence, and finally dried in a vacuum oven.
[0009] Step 2: dissolving 1,1'-ferrocenedicarboxylic acid in N,N-dimethylformamide at room temperature and stirring to obtain liquid A; dissolving nickel chloride hexahydrate in deionized water at room temperature and stirring to obtain liquid B; mixing liquid A and liquid B to obtain a mixed solution; adding the pretreated nickel foam to the mixed solution, transferring to a high-pressure reactor for hydrothermal reaction, and washing and drying the obtained product to obtain a precursor;
[0010] Step 3: placing the precursor in the upstream of the tubular furnace, placing dicyandiamide in the downstream of the tubular furnace, and performing two-stage calcination and pyrolysis gas diffusion in the tubular furnace under the protection of inert gas; cooling to room temperature after the reaction is completed to obtain an iron-nickel alloy material coated with carbon nanotubes grown in situ on nickel foam.
[0011] Preferably, in step 1, the concentration of the aqueous hydrochloric acid solution is 1 to 4 mol / L, and the ultrasonic cleaning time in each solvent is 15 to 45 min.
[0012] Preferably, in step 2, the usage ratio of 1,1'-ferrocenedicarboxylic acid, nickel chloride hexahydrate, N,N-dimethylformamide and deionized water is 0.2-1 mmol: 0.2-1 mmol: 3.2-16 mL: 1.6-8 mL.
[0013] Preferably, in step 2, the reaction temperature of the hydrothermal reaction is 120-130° C., and the insulation time is 10-14 h.
[0014] Preferably, in step 3, the conditions for the two-stage calcination pyrolysis gas diffusion are: first, heating to 350-400°C at a heating rate of 4-5°C / min, and keeping warm for 2-3h; then continuing to heating to 550-600°C at a heating rate of 4-6°C / min, and keeping warm for 5-6h.
[0015] Preferably, in step 3, the inert gas is at least one of argon and nitrogen.
[0016] Preferably, in step 1 and step 2, the drying condition is drying at 60-80° C. for 6-10 hours.
[0017] The carbon nanotube-coated iron-nickel alloy material grown in situ on nickel foam prepared by the present invention can be used to construct a Fenton-like reaction system to degrade organic pollutants. The degradation process includes the following steps:
[0018] Periodate and carbon nanotube-coated iron-nickel alloy material grown in situ on nickel foam are added to organic pollutants, and the reaction is stirred at room temperature to achieve complete degradation of the organic pollutants.
[0019] Preferably, the periodate comprises at least one of potassium periodate and sodium periodate.
[0020] Preferably, the organic pollutant includes but is not limited to at least one of golden orange II, methyl violet, methylene blue, neutral red, tetracycline hydrochloride, and oxytetracycline hydrochloride.
[0021] Preferably, the concentration of organic pollutants is 1-100 mg / L, and the ratio of organic pollutants to periodate is 1-100 mg:1 mmol.
[0022] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0023] 1. The present invention uses hydrothermal reaction and calcination gas diffusion method to make carbon nanotubes coated with iron-nickel alloy grow directly on the surface of nickel foam in situ without any binder or template. The advantages of in-situ growth preparation of materials compared to the use of binders and templates are mainly to improve conductivity, promote charge transfer, increase active sites, improve electronic structure, improve intrinsic catalytic activity, and simplify the preparation process. The preparation method of the present invention significantly improves the high temperature resistance, low temperature resistance and aging resistance of the material, reduces subsequent pollution problems, and greatly improves the conductivity and stability of the material. The entire preparation process of the present invention is simple and convenient, does not require additional energy, and is suitable for large-scale production.
[0024] 2. The present invention uses the calcined gas diffusion method to coat the iron-nickel alloy in the carbon nanotubes, optimizes the dispersion of active sites, makes the carbon nanotubes grow evenly on the surface of the iron-nickel alloy, and improves the specific surface area and catalytic activity of the catalyst. This method effectively solves the problem of easy detachment of metal atoms and ion leaching during the reaction, and achieves high catalytic performance through low metal content, thereby saving energy and reducing costs.
[0025] 3. The iron-nickel alloy material coated with carbon nanotubes grown in situ on nickel foam prepared by the present invention combines the triple advantages of metal alloys, carbon nanotubes and nickel foam, providing excellent conductivity and specific surface area. Its porous framework increases the available contact area and provides diversified transport channels for catalytic reactions, thereby significantly improving catalytic activity and application potential. The interaction between the active sites in the material and graphitized carbon promotes the generation of active species. This unique structure not only provides abundant high-activity sites, but also enhances electron transport through the carbon nanotube coating, preventing material agglomeration during long-term operation, thereby ensuring excellent durability. In addition, the conductive nickel foam reduces the electron transfer distance and resistance in the oxidation reaction.
[0026] 4. The material prepared by the present invention can efficiently activate periodate to generate active free radicals, thereby solving the problem of difficult degradation of organic pollutants in the environment. At the same time, the monolithic material design effectively overcomes the difficulty of separating and recycling traditional powder catalysts. The entire reaction process is simple to operate, reacts quickly, does not require light assistance, and the material is easy to recycle, with a high recycling rate, which is in line with the concept of green environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a SEM image of the iron-nickel alloy material coated with carbon nanotubes grown in situ on nickel foam prepared in Example 1 of the present invention;
[0028] Figure 2 This is a TEM image of the iron-nickel alloy material coated with carbon nanotubes grown in situ on nickel foam prepared in Example 1 of the present invention;
[0029] Figure 3 This is an EDS element scanning image of the iron-nickel alloy material coated with carbon nanotubes grown in situ on nickel foam prepared in Example 1 of the present invention;
[0030] Figure 4 The electrochemical impedance diagram of the in-situ grown carbon nanotube-coated iron-nickel alloy material on the nickel foam prepared in Example 1 of the present invention and the single metal element loaded nickel foam composite material as a comparison;
[0031] Figure 5 This is a graph showing the repeatability of the degradation of Golden Orange II by the carbon nanotube-coated iron-nickel alloy material grown in situ on nickel foam prepared in Example 1 of the present invention;
[0032] Figure 6 This is a graph showing the ICP-MS detection results of the iron-nickel alloy material coated with carbon nanotubes grown in situ on nickel foam prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0033] The embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. The following embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following embodiments.
[0034] Example 1
[0035] (I) Preparation of Iron-Ni Alloy Material Coated with Carbon Nanotubes Grown In Situ on Nickel Foam
[0036] The preparation method of the carbon nanotube-coated iron-nickel alloy material grown in situ on nickel foam in this embodiment is as follows:
[0037] 1. First, cut the nickel foam into small pieces with a length and width of 2 cm × 2.5 cm, then ultrasonically clean the nickel foam material in 1 mol / L hydrochloric acid aqueous solution, acetone, deionized water and anhydrous ethanol for 15 min respectively, and finally dry it in a vacuum oven at 60 ° C for 6 h.
[0038] 2. Dissolve 0.5mmol 1,1'-ferrocene dicarboxylic acid in 8mL N,N-dimethylformamide at room temperature and stir to obtain liquid A. Dissolve 0.5mmol nickel chloride hexahydrate in 4mL deionized water at room temperature and stir to obtain liquid B. Mix liquid A and liquid B evenly to obtain a mixed solution. Add the pretreated nickel foam to the mixed solution, transfer to a high-pressure reactor for hydrothermal reaction at 125°C for 12h, wash repeatedly with anhydrous ethanol and deionized water, and dry at 60°C for 6h to obtain a precursor.
[0039] 3. Place three pieces of precursors in the upstream of the tube furnace, place 1.2g of dicyandiamide in the downstream of the tube furnace, and gradually heat from room temperature to 400°C at a rate of 5°C / min under the protection of inert gas for 2 hours, and then heat to 570°C at a rate of 2°C / min for 5 hours. After the reaction is completed, cool to room temperature to obtain an iron-nickel alloy material coated with carbon nanotubes grown in situ on nickel foam.
[0040] Figure 1 This is a SEM image of the iron-nickel alloy material coated with carbon nanotubes grown in situ on the nickel foam prepared in this example. From the image, it can be seen that the carbon nanotubes grown on the surface of the nickel foam are clearly visible. Figure 2This is a TEM image of the iron-nickel alloy material coated with carbon nanotubes grown in situ on the nickel foam prepared in this embodiment. From the image, it can be clearly observed that the carbon nanotubes tightly wrap the iron-nickel alloy structure. It can be seen that the material prepared in this embodiment is a carbon nanotube structure coated on the surface of the nickel foam, and the iron-nickel alloy exists inside the carbon nanotubes. Figure 3 This is an EDS element scan of the iron-nickel alloy material coated with in-situ grown carbon nanotubes on nickel foam prepared in this embodiment. It can be seen from the figure that iron, nickel, nitrogen, carbon and oxygen elements are uniformly doped in the nickel foam, confirming that the material has an alloy structure.
[0041] Electrochemical impedance spectroscopy was performed on a CHI-660E electrochemical workstation: the carbon nanotube-coated iron-nickel alloy material grown in situ on nickel foam prepared in this example was used as the working electrode, the platinum electrode was used as the counter electrode, the Ag / AgCl electrode was used as the reference electrode, and 50 mmol / L Na 2 SO 4 The solution is the electrolyte and the charge transfer resistance of the working electrode is measured. Figure 4 The electrochemical impedance diagrams of the iron-nickel alloy material coated with carbon nanotubes in situ grown on nickel foam prepared in this embodiment and the single metal element loaded nickel foam composite material (prepared in the same way as in this embodiment, the only difference is that the amount of 1,1'-ferrocenedicarboxylic acid or nickel chloride hexahydrate is changed to 0) are shown. It can be seen from the diagram that the iron-nickel alloy material coated with carbon nanotubes in situ grown on nickel foam prepared in this embodiment has lower impedance than the single metal composite material and the nickel foam material, indicating that the bimetallic composite effectively reduces the impedance of the material, that is, improves the conductivity of the material.
[0042] (II) Degradation of organic pollutants
[0043] A 20 mg / L Golden Orange II solution was prepared to simulate organic pollutants (V=200 mL), and 1 mmol / L potassium periodate and a piece of carbon nanotube-coated iron-nickel alloy material grown in situ on nickel foam prepared in this embodiment were added. The reaction was carried out at 25° C. for 80 min. After testing, the removal rate of toxic organic pollutants was as high as 100%.
[0044] After completing one test, the carbon nanotube-coated iron-nickel alloy material grown in situ on the nickel foam was removed, rinsed with deionized water, and dried, and then the degradation experiment was carried out again using the same method to test its repeatability.
[0045] Figure 5 This is a repeatability experimental diagram of the degradation of Golden Orange II by the iron-nickel alloy material coated with carbon nanotubes grown in situ on nickel foam prepared in this embodiment. It can be seen from the figure that the prepared material still shows a good degradation effect after 4 repetitions, indicating that the prepared composite material has a stable effect, a firm distribution of active components and excellent anti-aging ability.
[0046] The ion leaching performance was characterized by directly measuring the concentration of iron and nickel ions in the solution after the reaction: 5 mL of the solution after 30 minutes of the above degradation reaction was added to 15 mL of 65-68% concentrated nitric acid and ultrasonicated for 30 minutes. 2 mL of the supernatant was diluted to 10 mL. The sample was detected by Agilent 7500 Isotope Chronology Laboratory-Laser Ablation Plasma Mass Spectrometer of Agilent Corporation of the United States. Figure 6 This is the ICP-MS graph of the iron-nickel alloy material coated with carbon nanotubes grown in situ on nickel foam prepared in this embodiment. It can be seen from the figure that the amount of iron ions leached after the reaction is only 13.17ug / L, and the amount of nickel ions leached is only 25.38ug / L, which solves the defects of metal ions easily falling off from the carrier and a large amount of ions leaching during the reaction.
[0047] Example 2
[0048] (I) Preparation of Iron-Ni Alloy Material Coated with Carbon Nanotubes Grown In Situ on Nickel Foam
[0049] The preparation method of the in-situ grown carbon nanotube-coated iron-nickel alloy material on nickel foam in this embodiment is the same as that in Example 1.
[0050] (II) Degradation of organic pollutants
[0051] A 20 mg / L methyl violet solution was prepared to simulate organic pollutants (V=200 mL), and 1 mmol / L potassium periodate and a piece of carbon nanotube-coated iron-nickel alloy material grown in situ on nickel foam prepared in this embodiment were added. The reaction was carried out at 25° C. for 80 min. After testing, the removal rate of toxic organic pollutants was as high as 100%.
[0052] Example 3
[0053] (I) Preparation of Iron-Ni Alloy Material Coated with Carbon Nanotubes Grown In Situ on Nickel Foam
[0054] The preparation method of the iron-nickel alloy material coated with carbon nanotubes grown in situ on nickel foam in this embodiment is the same as that in Example 1.
[0055] (II) Degradation of organic pollutants
[0056] A 20 mg / L neutral red solution was prepared to simulate organic pollutants (V=200 mL), and 1 mmol / L potassium periodate and a piece of carbon nanotube-coated iron-nickel alloy material grown in situ on nickel foam prepared in this embodiment were added. The reaction was carried out at 25° C. for 80 min. After testing, the removal rate of toxic organic pollutants was as high as 100%.
[0057] Example 4
[0058] (I) Preparation of Iron-Ni Alloy Material Coated with Carbon Nanotubes Grown In Situ on Nickel Foam
[0059] The preparation method of the iron-nickel alloy material coated with carbon nanotubes grown in situ on nickel foam in this embodiment is the same as that in Example 1.
[0060] (II) Degradation of organic pollutants
[0061] A 20 mg / L tetracycline hydrochloride solution was prepared to simulate organic pollutants (V=200 mL), and 1 mmol / L potassium periodate and a piece of carbon nanotube-coated iron-nickel alloy material grown in situ on nickel foam prepared in this embodiment were added. The reaction was carried out at 25° C. for 80 min. After testing, the removal rate of toxic organic pollutants was as high as 100%.
[0062] Example 5
[0063] (I) Preparation of Iron-Ni Alloy Material Coated with Carbon Nanotubes Grown In Situ on Nickel Foam
[0064] The preparation method of the iron-nickel alloy material coated with carbon nanotubes grown in situ on nickel foam in this embodiment is the same as that in Example 1.
[0065] (II) Degradation of organic pollutants
[0066] A 20 mg / L oxytetracycline hydrochloride solution was prepared to simulate organic pollutants (V=200 mL), and 1 mmol / L potassium periodate and a piece of carbon nanotube-coated iron-nickel alloy material grown in situ on nickel foam prepared in this embodiment were added. The reaction was carried out at 25°C for 80 minutes. After testing, the removal rate of toxic organic pollutants was as high as 100%.
[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an iron-nickel alloy material coated with carbon nanotubes grown in situ on nickel foam, characterized in that: Proceed as follows: Step 1: ultrasonically clean the nickel foam material in hydrochloric acid aqueous solution, acetone, deionized water and anhydrous ethanol in sequence, and finally dry it in a vacuum oven; Step 2: dissolving 1,1'-ferrocene dicarboxylic acid in N,N-dimethylformamide at room temperature to obtain solution A; dissolving nickel chloride hexahydrate in deionized water at room temperature to obtain solution B; Mix liquid A and liquid B evenly to obtain a mixed liquid; The pretreated nickel foam is added to the mixed solution, and the mixture is transferred to a high-pressure reactor for hydrothermal reaction, and the obtained product is washed and dried to obtain a precursor; Step 3: placing the precursor in the upstream of the tubular furnace, placing dicyandiamide in the downstream of the tubular furnace, and performing two-stage calcination and pyrolysis gas diffusion in the tubular furnace under the protection of inert gas; cooling to room temperature after the reaction is completed to obtain an iron-nickel alloy material coated with carbon nanotubes grown in situ on nickel foam.
2. The preparation method according to claim 1, characterized in that: In step 1, the concentration of the hydrochloric acid aqueous solution is 1 to 4 mol / L.
3. The preparation method according to claim 1, characterized in that: In step 2, the usage ratio of 1,1'-ferrocenedicarboxylic acid, nickel chloride hexahydrate, N,N-dimethylformamide, and deionized water is 0.2-1 mmol: 0.2-1 mmol: 3.2-16 mL: 1.6-8 mL.
4. The preparation method according to claim 1, characterized in that: In step 2, the reaction temperature of the hydrothermal reaction is 120-130° C., and the insulation time is 10-14 h.
5. The preparation method according to claim 1, characterized in that: In step 3, the conditions for the two-stage calcination pyrolysis gas diffusion are: first, heating to 350-400°C at a heating rate of 4-5°C / min, and keeping warm for 2-3h; then continuing to heat to 550-600°C at a heating rate of 4-6°C / min, and keeping warm for 5-6h.
6. The preparation method according to claim 1, characterized in that: In step 3, the inert gas is at least one of argon and nitrogen.
7. The preparation method according to claim 1, characterized in that: In step 1 and step 2, the drying condition is drying at 60-80° C. for 6-10 hours.
8. An iron-nickel alloy material coated with carbon nanotubes grown in situ on nickel foam obtained by the preparation method according to any one of claims 1 to 7.
9. An application of the carbon nanotube-coated iron-nickel alloy material grown in situ on nickel foam as claimed in claim 8, characterized in that: The material is used to construct a Fenton-like reaction system to degrade organic pollutants, and the degradation process includes the following steps: Periodate and carbon nanotube-coated iron-nickel alloy material grown in situ on nickel foam are added to organic pollutants, and the reaction is stirred at room temperature to achieve complete degradation of the organic pollutants.
10. The use according to claim 9, characterized in that: The periodate comprises at least one of potassium periodate and sodium periodate.
11. The use according to claim 9, characterized in that: The organic pollutant is at least one of golden orange II, methyl violet, methylene blue, neutral red, tetracycline hydrochloride and oxytetracycline hydrochloride.
Citation Information
Patent Citations
Porous carbon-iron-nickel alloy foamed nickel electrode and preparation method and application thereof
CN111498952A
NiPd nano-alloy catalyst, preparation thereof and application of NiPd nano-alloy catalyst in hydrogen reduction of hexavalent chromium
CN114950476A
Method for preparing iron-based carbon / foamed nickel composite catalyst based on waste lithium iron phosphate electrode material
CN116005191A
Carbon nanotube packaging alloy material catalyst as well as preparation method and application thereof
CN118059869A